Synthesis of N-thioacetyl gangliosides GM1 and GM3 - Isecke, Rainer; Brossmer, Reinhard; Sonnino, Sandro (Bioorganic & medicinal chemistry letters, 1995)
Reaction of de-N-acetyl gangliosides GM1 (1) and GM3 (2b) with methyl dithioacetate (3) afforded N-thioacetyl GM1 (1c) and N-thioacetyl GM3 (2c) with the oxygen of the acetamido group of N-acetylneuraminic acid residue replaced by sulfur.
Im Titel sind die Zahlen "1" und "3" tiefgestellt
Elektronische Reproduktion der Druck-Ausgabe 29. März 2000
Gesehen am 27.06.2024